Kepemimpinan Kepala Sekolah, Pembiayaan Pendidikan, Komite Sekolah, Lingkungan Sekolah Terhadap Kinerja Sekolah - Huda, Choirul; Kardoyo, Kardoyo (Business and Accounting Education Journal, 2021)
The purpose of this study is to know and analyze the influence of the principal leadership, education financing, school committes role, and the school environment on school perfomance. The type of this study was quantitative study. The research design employed was ex post facto research. The populations as many 37 at senior high school. This study employed area sampling technique. The method of data collection employed questionnaire and documentation. The technique of data analysis used descriptive analysis, path analysis, and sobel test. The results of the study show that there is a positive and significant influence on the quality of the process on the quality of graduates. There is a positive and significant influence of the principal's leadership on the quality of the process. There is a positive and significant effect of education financing on process quality as much as. There is a positive and significant influence on the role of the school committee on quality. There is a positive and significant influence on the school environment on the quality of the process. The quality of the learning process fully mediates the influence of the principal's leadership on the quality of graduates. The quality of the learning process fully mediates the effect of educational funding on the quality of graduates. The quality of the learning process fully mediates the influence of the role of the school committee on the quality of graduates. The quality of the learning process does not mediate the influence of the school environment on the quality of graduates.